The Critical (micro) Political Economy of Health - Jeverson Santiago (Al-Qanṭara, 2022)
The critical political economy of health offers different explanations for the social causes of health and the social factors determining the distribution of these causes. However, the relational, post-anthropocentric and monist ontology of the new materialisms overcomes this complexity, while retaining a critical focus. In this perspective, the social, economic and political relations of capitalism act upon bodies and other matter in everyday events, rather than as ‘social structures’. Using a conceptual toolkit of ‘affect’, ‘assemblage’, ‘capacity’ and ‘micropolitics’, the paper asks the question: ‘what does capitalism do?’ The re-analysis of the social and economic relations of capitalism in terms of a production-assemblage and a market-assemblage reveals not only the workings of capitalist accumulation, but also how previously-unremarked more-than-human affects in these assemblages simultaneously produce uncertainty, waste and inequalities. This micropolitical economy of health is illustrated with examples from recent research, including a critical assessment of health inequalities during the Covid-19 pandemic.